Empirical 3D model of the conch of the Middle Jurassic ammonite microconch Normannites: its buoyancy, the physical effects of its mature modifications and speculations on their function - Tajika, Amane; Naglik, Carole; Morimoto, Naoki; Pascual-Cebrian, Enric; Hennhöfer, Dominik K.; Klug, Christian (Historical biology, 2015)
A 3D model of the Middle Jurassic ammonoid Normannites with an apertural modification from Thürnen, Switzerland, was constructed using physical-optical tomography. It was tested to determine whether the formation of the apertural modification affected shell orientation, to estimate buoyancy regulation and to reconstruct the mode of life of this ammonoid. No drastic postural changes occurred between the 3D models that excluded and included lappets, suggesting that the lappets were not formed to change the syn vivo shell orientation and, in turn, locomotion. We speculate that these adult shell modifications served to protect the soft parts during the reproduction period. Buoyancy calculations based on the model assume that ammonoids were positively buoyant when the phragmocone was devoid of liquid. When 31% of the entire phragmocone was filled with liquid, the living animal would have reached neutral buoyancy in contrast to 27% of cameral liquid filling when the weight of the aptychi is included. Provided that smaller ammonoids had more cameral liquid than bigger ammonoids, such as the modern Nautilus, Normannites examined in this study would have been able to maintain neutral buoyancy and might have had a demersal, nektobenthic or nektonic habitat somewhere in the water column.